The Effect of Sintering Time on Surface Morfology of Pb-Doped Bi-2223 Oxides Superconductors Prepared by the Solid State Reaction Methods at 840 oC - Yufita, Evi; ., Nurmalita (Aceh Physics Society, 2016)
This study was investigating the effect of sintering time (30 h, 32 h, and 34 h) on surface morphology of Pb-doped Bi-2223 oxides of superconductors prepared by the solid-state reaction method at 840 oC. The superconductor was characterized by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Â In the present study, phase purity, volume fraction, surface morphology, texturing, crystallinity, grain connectivity and grain size of the bulk samples are found and compared with each other. The enhancement in the sintering time is confirmed that it will decrease Bi-2223 phase fraction and increase the impurity of the samples. SEM images shows that the sample has the best crystallinity, grain connectivity and largest grain size. Based on the present results, it is conclude that the surface morphological is improving with the increasing of the sintering time.